PENGARUH MEDIA TANAM TERHADAP VIABILITAS DAN PERTUMBUHAN BENIH PEPAYA CALIFORNIA (Carica papaya L.) - Bagus Putu Udiyana; Cokorda Javandira; I Ketut Sumantra; Komang Dean Ananda; Ni Gusti Ayu Dona Agustini (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
The purpose of this study was to determine the effect of planting media and comparison of appropriate planting media on the viability and growth of California papaya (Carica papaya L.) seeds. This research used a Randomized Block Design (RAK) with one factor comparison of planting media with 5 level of treatments, namely (P0) 12 kg planting media soil with no sand, treatment (P1) planting media of 12 kg of sand with no soil, treatment (P2) planting media of 6 kg of soil and 6 kg of sand, treatment (P3) planting media of 8 kg of soil and 4 kg sand, treatment (P4) planting media of 4 kg of soil and 8 kg of sand, and each treatment was repeated 5 times to obtain 25 treatments. Planting media had a significant to very significant effect on the parameters of fresh weight of roots but gave a significant effect on parameters of growth speed, plant height, the number of leaves, fresh weight above the soil, oven-dry weight above the soil, and oven-dry weight of roots. Planting media had very significant effect on the viability of papaya seeds by producing the fastest growing speed in the P3 treatment (10,96 dap). Planting media treatment 8 kg of the soil and 4 kg of sands with composition 2:1 (P3) gave the highest yield of fresh weight above the soil of 16.60 (g), oven-dry weight above the soil of 2.00 (g) and oven-dry weight of roots of 0,70 (g).